Meta-analyses on studies about the identification and attention of the gifted and talented in Peru - Blumen, Sheyla (2004)
Are gifted and talented identification programs scientifically based, fair and unbiased? Aregifted enrichment programs effective? Financia! pressures from NGOs and prívate founda tions, changes in national educational policies, as well as multicultural issues, are forcing psychologists and educators to face these questions. Our review discusses the important changes that have begun to alter the gifted and talented field in Latin America, especially in Peru. It describes recent empirical studies in multicultural populations and analyses the impact of the intervention programs, both, on the teacher training leve! as well as on thegifted enrichment programs,  which are being developed in the region.